(untitled) (Journal of the Bangladesh Agricultural University, 2012)
Efficacy of Bion (benzothiodiazole), Amistar (azoxystrobin) and Tilt (propiconazole) was evaluated for controlling Brown spot and Narrow brown spot of rice cv. BR11 (Mukta). Bion, Amistar and Tilt @ 50 mg/L, 1 ml/L and 1 ml/L, respectively were sprayed at tillering and ear initiation stages that resulted in marked reduction of Brown spot and Narrow brown spot. Bion, Amistar and Tilt significantly increased number of grains/ear and number of healthy grains/ear by reducing number of diseased grains/ear. Bion, Amistar and Tilt resulted in 25.87, 32.17 and 26.76% higher grain yield, respectively over the untreated control when sprayed at tillering stage. DOI: http://dx.doi.org/10.3329/jbau.v9i2.10986 J. Bangladesh Agril. Univ. 9(2): 201204, 2011